2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5335140
|View full text |Cite
|
Sign up to set email alerts
|

SHIMMER: A new tool for temporal gait analysis

Abstract: Development of a flexible wireless sensor platform for measurement of biomechanical and physiological variables related to functional movement would be a vital step towards effective ambulatory monitoring and early detection of risk factors in the ageing population. The small form factor, wirelessly enabled SHIMMER platform has been developed towards this end. This study is focused assessing the utility of the SHIMMER for use in ambulatory human gait analysis. Temporal gait parameters derived from a tri-axial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 10 publications
0
30
2
Order By: Relevance
“…Of the 38 articles included in this review 23 articles utilised accelerometers and/or gyroscopes during running gait to identify coach orientated kinematic parameters (See Table 1.2). 48 Bergamini et al 17 Bichler et al 18 Cooper et al 19 Hausswirth et al 11 Heiden et al 49 Le Bris et al 31 Lee et al 32 Lee et al 47 McCurdy et al 50 McGrath et al 13 Mercer et al 35 Mercer et al 36 Neville et al 51 Neville et al 52 O'Donovan et al 20 Purcell et al 53 Stohrmann et al 22 Stohrmann et al 21 Stohrmann et al 23 Tan et al 14 Wixted et al 54 Yang et al 15 Step/Stride Frequency…”
Section: Coach Orientated Kinematic Output Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 38 articles included in this review 23 articles utilised accelerometers and/or gyroscopes during running gait to identify coach orientated kinematic parameters (See Table 1.2). 48 Bergamini et al 17 Bichler et al 18 Cooper et al 19 Hausswirth et al 11 Heiden et al 49 Le Bris et al 31 Lee et al 32 Lee et al 47 McCurdy et al 50 McGrath et al 13 Mercer et al 35 Mercer et al 36 Neville et al 51 Neville et al 52 O'Donovan et al 20 Purcell et al 53 Stohrmann et al 22 Stohrmann et al 21 Stohrmann et al 23 Tan et al 14 Wixted et al 54 Yang et al 15 Step/Stride Frequency…”
Section: Coach Orientated Kinematic Output Parametersmentioning
confidence: 99%
“…All three studies identified different methods to analyse angular velocity for ground contact. O'Donovan et al 20 used a method by Aminian et al 57 which utilised mediolateral angular velocity. Bichler et al 18 stated that foot contact occurred between the first and last samples of angular velocity below 1rad in the respective foot and McGrath et al 13 utilised an algorithm which calculated thresholds based on angular velocity about the y-axis …”
Section: Temporal Parameters Secondary Coach Orientated Kinematic Pamentioning
confidence: 99%
See 1 more Smart Citation
“…Wearable devices (such as gyroscopes, pressure sensors, etc.) have been also proposed [12,13], especially for ambulatory measurements in home settings. Despite their low cost and lightweight, wearable sensors must be correctly placed by a technical expert, and are not accurate due to signal noise and drift.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, such systems are only suitable for laboratory settings. Wearable sensors systems are more suitable for ambulatory measurements in home settings as they are small, lightweight, mobile and less expensive [14], [15]. But these sensors must be placed correctly and securely [16], and must account for gravity, noise and signal drift [5].…”
Section: Introductionmentioning
confidence: 99%